Synthesis a Number of Heterocyclic Compounds Derived From Levofloxacin - Ekram Abdullah Basheer; Kalid Matny Al-jaanaby; Feras Shauki Al-joboury (Tikrit Journal of Pure Science, 2023)
In this paper, the preparation a number of heterocyclic compounds five membered rings like oxadiazole, imidazolidine, thiozolidine, tetrazole, azetidine 2-on. Hydrazide (1) was synthesized from the reaction of levofloxacin with hydrazine hydrate. Hydrazone compounds  (2-9) were synthesized from the  reaction (1) with a number of aldehydes, and 3-acetyl-1,3,4-oxadiazol (10-17) was prepared from the reaction of  hydrazones (2-9) with acetic anhydride, 5-oxo-2-aryl imadazoldine derivative (18-25) were prepared from the reaction of  hydrazone derivatives (2-9) with glycine, while the reaction of hydrazone with thioglygolic acid gave 4-oxo-2-aryl-thiozolidine (26-33),tetrazole derivative(34-41)prepared from the reaction of hydrazone(2-9) with sodium azide in tetrahyro furan.azetidine-2-on(42-49)with chloro acetyl chloride in DMF and and in the presence of triethyl amine  these compounds were characterized on bases of spectral and physical data.